Reaction Speed and Blocking Ability in Volleyball Extracurricular Participants at High School - Arifuddin Usman; Nafi Basram; Arimbi Arimbi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Blocking ability is one of the technical skills that greatly determines a team's success in volleyball. Blocking effectiveness is influenced by various physical components, including lower leg explosiveness and reaction speed. However, empirical studies examining the relationship between these two physical variables in high school volleyball extracurricular participants are still limited. Therefore, this study aims to analyze the relationship between lower leg explosiveness and reaction speed with blocking ability. This study used a quantitative correlational design with a population of 20 volleyball extracurricular participants at High School 8 Bulukumba using a total sampling technique. Lower leg explosiveness was measured using a vertical jump test, reaction speed using a visual reaction test, and blocking ability using a volleyball blocking skills test. Data was analyzed using Pearson Product Moment correlation. The results showed a positive and significant relationship between lower leg explosiveness and reaction speed with blocking ability. The correlation coefficient (r) value of 0.770 indicates a strong relationship, with the simultaneous contribution of both variables amounting to 59.3% of the variation in blocking ability. Leg explosiveness has been shown to play a crucial role in producing an optimal vertical jump, while reaction speed determines the accuracy of timing and hand position when facing an attack. This study concludes that the synergy between explosive and responsive physical components is the primary foundation for technical success in modern volleyball dynamics at the high school level. Increasing explosive power and reaction speed is essential for optimizing blocking performance in high school volleyball extracurricular programs.